Proposed Mechanisms of Heart Failure Developing in SARS-CoV-2 Infected Patients - Putra, Iwan Cahyo Santosa; Henrina, Joshua; Gunawan, Hoo Felicia Hadi; Cahyadi, Irvan; Suciadi, Leonardo Paskah (Cardiology and Cardiovascular Medicine, 2020)
Coronavirus Disease of 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). On March 12, 2020, the World Health Organization (WHO) announced the pandemic state of COVID-19. Later, this disease has already known to affect multiple organs, including the heart. Therefore, higher morbidity and mortality occurred in elderly and patients with combined comorbidities. Based on the source of insults of heart failure risk, it can be classified into extrinsic and intrinsic risk. Extrinsic risks are anything that is related other than the virus itself, particularly treatments that are needed to deal with COVID-19 but subsequently affect the cardiovascular system. In contrast, the intrinsic risks are anything related to SARS-CoV-2 infection and its impact on the cardiovascular system. Furthermore, the pathophysiology of heart failure pertaining to cardiac output can be divided into three components, which are preload, myocardial contractility, and afterload. These components do not exclusively affect the left ventricle function but also the right ventricle. In addition, the risks of heart failure due to SARS-CoV2 infection exist both in the short and long term, based on their time onset. In this literature review, we propose the pathophysiology of the alteration of each of these components, which ultimately ends in heart failure.